Improving probiotic (Lactobacillus casei) viability by encapsulation in alginate-based microgels: Impact of polymeric and colloidal fillers. (January 2023) - Li, Qian; Lin, Hongyi; Li, Jing; Liu, Lu; Huang, Jialu; Cao, Yi; Zhao, Tiantian; McClements, David Julian; Chen, Jun; Liu, Chengmei; Liu, Jiyan; Shen, Peiyi; et al.
Abstract: Biopolymer microgels (hydrogel beads) can be used to improve probiotic stability during food storage and gastrointestinal passage. In this study, the impact of including natural polymeric and colloidal fillers on the viability of Lactobacillus casei encapsulated in calcium alginate microgels was examined. The polymeric filler was polysaccharides isolated from Choerospondias axillaris fruit peel (CP) and the colloidal filler was oil-in-water emulsion stabilized by CP. Results showed that addition of CP or CP coated lipid droplets significantly increased the antioxidant activity but reduced the apparent viscosity of the alginate solutions. Encapsulation of the probiotics in pure calcium alginate microgels reduced their viability (≈ 0 log CFU g −1 after 24 h). The inclusion of the polymeric or colloidal fillers within the microgels eliminated this negative effect. Moreover, they enhanced probiotic viability under simulated gastrointestinal tract conditions (> 7.0 log CFU g −1 ). The calcium alginate microgels containing CP had the highest probiotic viability (7.42 ± 0.08 log CFU g −1 ) after 20 days storage. Our results indicated that simple calcium alginate microgels are not effective at protecting Lactobacillus casei during storage or gastrointestinal passage. However, incorporation of suitable polymeric or colloidal fillers can significantly enhance their viability. Graphical abstract: Image 1 Highlights: Microgels were formed by alginate and C. axillaris peel polysaccharides (CP). Pure calcium alginate microgels encapsulation reduced probiotic viability. Calcium alginate + CP microgels enhanced probiotic viability during storage. Adding of CP or CP coated oil droplet improved probiotic gastrointestinal stability.